Meningkatkan Daya Tarik Restoran dengan Kuliner Halal : Strategi Menu di Hotel Yamamomo Awakankou, Jepang - Putri, Karisma Amalinda; Widagdo, Susmono (KIRYOKU, 2024)
Yamamomo Restaurant at Awakanko Hotel is currently facing challenges in meeting customer demands for halal menu options. One of the reasons for the limited variety of halal menus is the restricted availability of ingredients, which are only accessible during certain periods. This has led to complaints from customers. This study aims to analyze the strategies of Yamamomo's management in increasing the variety and availability of halal menus as an effort to enhance the restaurant's appeal, meet customer demands, and improve their satisfaction. The method used is qualitative, analyzing management policies through interviews with restaurant staff and tourists. The results show that by changing the procurement strategy and expanding the variety of halal menus, Yamamomo Restaurant has succeeded in providing a more diverse halal menu available at all times. Additionally, promoting the halal label to tourists strengthens Yamamomo's position as an inclusive restaurant that is responsive to customer needs. This effort highlights the importance of flexibility in restaurant management and menu innovation to enhance overall appeal and service quality.